2014
DOI: 10.1186/1741-7015-12-15
|View full text |Cite
|
Sign up to set email alerts
|

Global collaborative networks on meta-analyses of randomized trials published in high impact factor medical journals: a social network analysis

Abstract: BackgroundResearch collaboration contributes to the advancement of knowledge by exploiting the results of scientific efforts more efficiently, but the global patterns of collaboration on meta-analysis are unknown. The purpose of this research was to describe and characterize the global collaborative patterns in meta-analyses of randomized trials published in high impact factor medical journals over the past three decades.MethodsThis was a cross-sectional, social network analysis. We searched PubMed for relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 39 publications
3
29
1
Order By: Relevance
“…In addition, restrictions and difficulties in conducting clinical research in resource-poor situations result in the exclusion of many of these countries from the planning, conduct and publication of RCTs [67][68][69]. As might be expected, our results support previous findings that low-and middle-income countries [31,70,71] had minimal contributions in articles published in major medical journals. For example, a previous study [70] showed that most of the authors of original papers published in five high-impact general medical journals (including The New England Journal of Medicine, The Lancet, JAMA, The BMJ and Annals of Internal Medicine) were more frequently affiliated with institutions in the same country as the journal.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, restrictions and difficulties in conducting clinical research in resource-poor situations result in the exclusion of many of these countries from the planning, conduct and publication of RCTs [67][68][69]. As might be expected, our results support previous findings that low-and middle-income countries [31,70,71] had minimal contributions in articles published in major medical journals. For example, a previous study [70] showed that most of the authors of original papers published in five high-impact general medical journals (including The New England Journal of Medicine, The Lancet, JAMA, The BMJ and Annals of Internal Medicine) were more frequently affiliated with institutions in the same country as the journal.…”
Section: Discussionsupporting
confidence: 89%
“…Specifically, one researcher (AA-A) checked the names by which an individual author appeared in two or more different forms (for example, "John McMurray" or "John J. McMurray" or "John J.V. McMurray") using coincidence in that author's place(s) of work as the basic criterion for normalisation (for example, University of Glasgow, Scotland, United Kingdom) [31], and a second researcher (FC-L or RA-B) verified the data. A threshold of 30 articles was applied to review 200 names by which an individual author appeared in two or more different forms.…”
Section: Data Extraction and Normalisationmentioning
confidence: 99%
“…When performed well and reported transparently, incorporating explicit and detailed methods and results, they produce information that can have undoubtedly major impact on medical practice. 2,3 In recent years, there has been accumulating evidence concerning the association of statins with incident cataracts. Randomized clinical trials have not identified an association between statins and cataracts, on the contrary, observational studies have reported conflicting associations between statin use and incident cataracts.…”
mentioning
confidence: 99%
“…The small contribution of non‐U.S.A. and non‐European researchers is particularly noteworthy, because in many of these countries, medicine and clinical training remain underdeveloped . These results should be biased as the British Journal of Dermatology , Acta Dermato‐Venereologica and Experimental Dermatology are European journals and the Journal of Investigative Dermatology , JAMA Dermatology and Journal of the American Academy of Dermatology are U.S. journals.…”
Section: Region Of Origin Study Population Sources Of Funding and Smentioning
confidence: 99%
“…The small contribution of non-U.S.A. and non-European researchers is particularly noteworthy, because in many of these countries, medicine and clinical training remain underdeveloped. 14 The funding rates for original research have increased in the literature over the past decade. 11,12 Our study shows that three out of four RCTs in the analysed journals received financial support, and in more than 50% of cases, such support came from industry.…”
mentioning
confidence: 99%